2017
DOI: 10.1002/cam4.1270
|View full text |Cite|
|
Sign up to set email alerts
|

Pretreatment C‐reactive protein/albumin ratio is associated with poor survival in patients with stage IBIIA cervical cancer

Abstract: Previous studies have shown that the C‐reactive protein/albumin ratio (CAR) is a prognostic indicator in multiple types of carcinomas. This study is the first to evaluate the prognostic significance of CAR in stage IB‐IIA cervical cancer patients treated with radical surgery, as well as that of several other inflammation‐based factors, including the neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and prognostic nutritional index (PNI). A total of 235 patients were enrolled in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 33 publications
4
44
1
1
Order By: Relevance
“…Recently, an increasing amount of research has been focusing on the effects of systemic inflammatory response (SIR) on oncogenesis, and such research has revealed that there is a significant relationship between SIR and poor tumor-specific survival in numerous cancers. [9][10][11] In particular, the neutrophil to lymphocyte ratio (NLR), which is considered as a biomarker of SIR, has emerged as an independent prognostic factor for biliary tract cancer in operable patients and in advanced disease patients undergoing adjuvant therapy. 12,13 The lymphocyte to monocyte ratio (LMR) is another biomarker of SIR, with a combination of lymphocyte count and monocyte count.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing amount of research has been focusing on the effects of systemic inflammatory response (SIR) on oncogenesis, and such research has revealed that there is a significant relationship between SIR and poor tumor-specific survival in numerous cancers. [9][10][11] In particular, the neutrophil to lymphocyte ratio (NLR), which is considered as a biomarker of SIR, has emerged as an independent prognostic factor for biliary tract cancer in operable patients and in advanced disease patients undergoing adjuvant therapy. 12,13 The lymphocyte to monocyte ratio (LMR) is another biomarker of SIR, with a combination of lymphocyte count and monocyte count.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, one concerning cervical cancer was disposed separately cause of providing HRs and survival outcomes for patients with two different treatments [21]. As a consequence, fifteen, nine, and four publications regarding to cervical [19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34], ovarian [35][36][37][38][39][40][41][42][43], and endometrial cancer [44][45][46][47] were enrolled, respectively.…”
Section: Literature Search Results and Characteristicsmentioning
confidence: 99%
“…36 Prior studies have shown that nutrient deficiency and systematic inflammatory response might play a critical role in the pathogenesis and progression of human carcinomas and were correlated with inferior prognosis in patients undergoing resection for solid tumors. 8,[37][38][39] Zheng et al have demonstrated that ALB is an independent prognostic indicator in early operable cervical cancer. 40 Moreover, a recent published article found that high levels of ALP could influence tumorigenesis and predict outcomes in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, certain laboratory indexes have been validated as prognostic indicators in cervical cancer, including C-reactive protein/albumin ratio (CAR), neutrophil-tolymphocyte ratio (NLR) and prognostic nutritional index (PNI). [8][9][10] The albumin (ALB) to alkaline phosphatase (ALP) ratio (AAPR) was first revealed as a prognostic index for hepatocellular carcinoma in 2015 as another available indicator for assessing the nutritional status, inflammation level, and immune response. 11 Subsequently, it has been reported as a novel prognostic factor in different malignant carcinomas, including nasopharyngeal carcinoma, pancreatic ductal adenocarcinoma, breast cancer, lung cancer, and cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%